Criteria for Desirable Structural Changes in Market Economies - Piotr WALĄG; Sylwester TABOR (Communications of International Proceedings, 2020)
OECD research into the production structures of highly developed countries for the years 1950-1995 shows that they are subject to the phenomenon of agrarianisation, industrialisation, stabilisation of industry's share of GDP, deindustrialisation and servicing. The most recent research of the economies of the catching up countries for the years 1995 -2020 has shown that the course of these processes may have different patterns, and the direction of structural changes, as well as economic effects. The aim of the article is to define the criteria for the desired structural changes, and to assess the difference between economies in the real structure of the economy, that is to say the course of economic evolution processes. In its initial part, the evolution of changes in the structure of employment (evolution of the economy) is presented in the context of its directions and main determinants. In the further part, the role and importance of industry in the structural changes of market economies is described. In the final part, different from the literature presented so far, the assessment of structural changes in the context of their economic consequences is outlined.
Keywords: Prevalent phenomena; prevalent factors; real price; agrarian era; evolution of economy; allocation of production factors.